The risk of acute disseminated encephalomyelitis (ADEM) following covid-19 vaccination in England: A self-controlled case-series analysis - Julia Stowe; Jamie Lopez-Bernal; Nick Andrews (Human Vaccines & Immunotherapeutics, 2024)
ABSTRACTAcute disseminated encephalomyelitis (ADEM) has been identified as an Adverse Event of Special Interest in the COVID-19 vaccine programme due to its long-standing temporal association with a wide range of other vaccines. Case reports of ADEM shortly following COVID−19 vaccination have now been documented.    There were 217 ADEM admissions in 215 individuals in the period 8th December 2020 to 31st March 2023. An increased risk of ADEM following the first dose of ChAdOx1 vaccine was observed (relative incidence (RI) = 3.13, 95% Confidence Interval (CI) [1.56–6.25]) with a vaccine attributable risk of 0.39 per million doses. When doses 1 and 2 were combined this increased risk remained just significant (1.96 [95%CI 1.01–3.82]). No significant increased risk was observed with any other vaccine or dose. This small, elevated risk after the first dose of ChAdOx1-S vaccine demonstrates how large national electronic datasets can be used to identify very rare risks and provides reassurance that any risk of ADEM following the ChAdOx1-S COVID-19 vaccination is extremely small. Given the rarity of this risk, further studies in settings with access to data on large populations should be carried out to verify these findings.